A prospective study on the administration and titration of oxygen therapy in mechanically ventilated patients - Saurabh Chandrakar; Ankit Agarwal; Gaurav Jain; R Udhayachandhar; Davis Cherian; Nupur B. Patel (Journal of Anaesthesiology Clinical Pharmacology, 2025)
Background and Aims: Medical oxygen (O2) is a lifesaving therapy in the intensive care unit (ICU). However, overzealous use and poorly defined O2 targets in ICU patients can increase the risk of hyperoxemia. We aimed to assess the administration and titration of O2 therapy in ICU patients requiring invasive mechanical ventilation (IMV) support. Material and Methods: In this prospective observational study, all adult patients requiring IMV for more than 24 hours were included over 1 year (December 2020–November 2021). Patients who refused to give consent or required IMV support for less than 24 hours, did not have arterial blood gas data, were at risk for imminent death, or required extracorporeal membrane oxygenation or hyperoxemia therapy were excluded. We calculated the incidence of hyperoxemia (SpO2 > 98%), physicians’ response to hyperoxemia, and factors associated with hyperoxemia. Multivariable logistic regression (MLR) analysis was done to assess factors associated with hyperoxemia. Results: Among 400 recruited patients and 4631 observations, 211 patients and 1669 observations had hyperoxemia. In 398 observations, oxygen was decreased. Physicians were reluctant to decrease oxygen when hyperoxemia was observed at lower inspired oxygen (χ2 = 182.1, P value < 0.001). On MLR analysis, the duration of IMV, minute ventilation, and inspired and partial pressure of oxygen were statistically significantly associated with hyperoxemia. Conclusions: Hyperoxemia was observed in approximately one-third of observations noted in mechanically ventilated patients. Physicians were reluctant to decrease oxygen when hyperoxemia was encountered at lower inspired oxygen.